In-vivo Three-dimensional Characteristics of Bowman's Layer and Endothelium/Descemet's Complex Using Corneal Microlayer Tomography in Healthy Subjects. (2nd June 2020) - Eleiwa, Taher K.; Elsawy, Amr; Syed, Zeba A.; Roongpoovapatr, Vatookarn; Sayed, Ahmed M.; Yoo, Sonia H.; Abou Shousha, Mohamed
ABSTRACT: Purpose : To characterize the three-dimensional (3D) thickness profile and age-related changes of Bowman's layer (BL), and endothelium/Descemet's membrane (En/DM) complex among healthy individuals using Corneal Microlayer Tomography (CML-T), and to describe its repeatability and accuracy. Methods : Sixty-six eyes of 41 healthy volunteers; 27 eyes (< 40 years old), and 39 eyes (>40 years old) were imaged using HD-OCT. Automatic and manual segmentation of the corneal layers was performed, and 3D thickness maps were generated, using custom-built CML-T software. A regional analysis of mean thickness parameters between the 2 age groups was performed. A regression analysis was used to assess the correlation between age, and thickness maps. Intraclass Correlation Coefficients (ICC), Coefficients of Variation (COV), and Bland-Altman plots were used to assess the reliability of the repeated measurements in 198 locations. Results : CML-T successfully mapped the BL and En/DM in all included eyes. Thickness maps showed a significant increase in corneal thickness (CT), BL thickness (BMT), and En/DM complex thickness (DMT) toward the periphery with a mean difference 28 µm ( p < .001), 1.1 µm ( p < .001), and 1.4 µm ( p < .001), respectively. There was a strong correlation between age and central DMT (r = 0.61; p < .001), while there was no correlation between age and both CT, and BMT. ICC values ranged from 0.9 (BMT) to 0.997 (DMT), and from 0.808 (BMT) to 0.979 (CT) for intraoperator repeatability of manual measurements, and the accuracy of auto matic measurements, respectively. COV values were lower than 7.5% in all cases. Conclusion : CML-T is a novel tool that can generate 3D-thickness maps of both BL and En/DM. CT, BMT, and DMT increase toward the periphery in healthy corneas. DMT increases with aging, while BMT does not. We also report excellent repeatability, accuracy and good agreement between automatic and manual measurements.